Is the PEGY ratio better than PEG ratio to measure return premium? A case of the Indian Banking sector - Sharma, Mr Bhumiswor; P, Dr Srikanth (The journal of contemporary issues in business and government, 2021)
Purpose: This study is an attempt to examine whether the return premium promised by Peter Lynch using PEGY benchmark (P<1 & P>0) has any value addition to the banking sector in India over PEG benchmark. The study tests the relationship between the return premium using PEGY, PEG ratios and the Indian banking sector. This study also examines the relationship between PEGY, PEG sorted portfolio returns and CSR activities in the Indian Banking sector. Design/methodology/approach: The paper analyses all the banking companies listed on the NSE-500 for the last 20 years, from March 2000 to March 2020. The study used CAPM regressions and is carried out on each portfolio using the common "excess return" form of the single-factor model equation to examine the existence of a full sample period as well as two sub-period return premiums. Findings: The empirical findings of the study indicated that there is a statistically significant difference in PEGY and PEG benchmark returns. The results also suggest that there is a positive monthly return premium in PEGY1 sorted portfolio both in the full sample as well as two sub-sample periods. Results of this study confirmed that the PEGY sorted portfolio is better than the PEG sorted to measure the return premium in the Banking sector. This research study also claims that there is no significant relationship between the PEGY, PEG sorted portfolio returns and CSR activities in the Indian Banking sector.